Past has never passed. Museum, an apparatus for the soul - Susanna Pisciella (Festival dell'Architettura Magazine, 2020)
This text attempts to visualize the substantial passage that led from the traditional conception of museum to the current one. I.e. from the museum as a real place, architecture, to the museum as dematerialized space, digital input. Architecture changes as the person changes, passing from a concave, contemplative attitude towards the world to a convex attitude, always active, always consuming. The participatory protagonism guaranteed by the over-stimulation of the interactive collections of the new museums has neutralized the architecture and, with this, the experience that traditionally was renewed within these places. The text contains some examples of museums that nowadays attempt to regenerate the original cognitive relationship, through the return of three singularities: of architecture, of the person, of the inner landscape, which incorporates the two previous ones. The museum as an apparatus for experience, for the expansion of the soul.